PENINGKATAN KAPASITAS SUMBERDAYA MANUSIA BAGI PETANI KERAMBA JARING APUNG DESA BATULAYANG KECAMATAN CILILIN KABUPATEN BANDUNG BARAT - Mira Veranita; R. Oke Andikarya; Yudhi Yudistira; Rajuman Rajuman; Dadan Hendayana; Regina Nurfitriyani Anissa (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M), 2023)
This Community Service Program is carried out to support the efforts of Floating Net Cages (KJA) Farmers in Batulayang Village, Cililin District, West Bandung Regency to overcome the problems they face related to the declining yields of KJA fish farming which has become a life-sustaining business. The priority problems faced are: the low knowledge and skills of farmers regarding business management, entrepreneurship and marketing management. And also the low knowledge of farmers about fish farming which results in less than optimal results and also has a serious impact on environmental pollution, especially lake water pollution. The solution and method of this PKM activity is to provide education in the form of training and education to farmers, thereby increasing motivation, increasing the knowledge and skills of farmers in business management, marketing, as well as knowledge about fish farming as well as providing assistance so that what has been delivered becomes sustainable technology. thereby increasing the quality and quantity of fish thereby increasing the income of farmers.